1997
DOI: 10.5326/15473317-33-4-320
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy of incompletely resected, moderately differentiated mast cell tumors in the dog: 37 cases (1989-1993)

Abstract: Thirty-seven dogs with moderately differentiated, cutaneous mast cell tumors had incomplete surgical excisions as determined by histopathology, but no gross evidence of tumor. All dogs were irradiated to a total dose of between 46.2 and 48.0 Gy using either an orthovoltage source (n = 20) or a linear accelerator (megavoltage) (n = 17). Radiation was delivered to an area bordered by margins of 3 cm or greater around the surgical scar. The mast cell tumors had not recurred in 97% of dogs by one year after radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
1
5

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 0 publications
3
60
1
5
Order By: Relevance
“…[3][4][5] In this study, a smaller number of well-differentiated and a larger number of intermediate-and poorly differentiated MCT were represented than in previous reports, in which all tumor locations were included. 4,15,22,23 This difference might represent a shift of grading criteria from earlier studies, or it might represent a true influence of location on tumor grade. An earlier study with similar grading criteria reported a distribution of grades comparable to this study when tumors of the trunk and extremities were combined.…”
Section: Discussionmentioning
confidence: 96%
“…[3][4][5] In this study, a smaller number of well-differentiated and a larger number of intermediate-and poorly differentiated MCT were represented than in previous reports, in which all tumor locations were included. 4,15,22,23 This difference might represent a shift of grading criteria from earlier studies, or it might represent a true influence of location on tumor grade. An earlier study with similar grading criteria reported a distribution of grades comparable to this study when tumors of the trunk and extremities were combined.…”
Section: Discussionmentioning
confidence: 96%
“…Rates of local recurrence with adjuvant radiation therapy have been reported to be 5, 14, and 20%. [21][22][23] Although the rates of local recurrence of studies in which no adjuvant treatments were performed cannot be compared statistically to those in which adjuvant treatments were administered, the rates are not very different and raise the question of the efficacy of adjuvant therapies. Because chemotherapy and especially radiation therapy are associated with considerable morbidity, establishing their efficacy becomes crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Also incompletely removed grade 2 MCTs were satisfactory treated by orthovoltage and megavoltage radiation (32). However, some caution is justified since "incomplete surgery" is certainly not always followed by local recurrence (46,77,78 It is striking that in three studies (46,77,78) incompleteness of therapy, defined by the presence of tumour cells in the margins of the surgical specimens, was not always followed by local recurrence.…”
Section: B Radiotherapy Alone or In Combination With Other Therapy Mmentioning
confidence: 99%
“…Radiotherapy has been administered to achieve total control of incompletely removed or locally recurrent MCTs (32,57,101,114).…”
Section: B Radiotherapy Alone or In Combination With Other Therapy Mmentioning
confidence: 99%